2017
DOI: 10.1002/cvj.12050
|View full text |Cite
|
Sign up to set email alerts
|

Stories Matter: Narrative Themes of Counselor Educators' Religious and Spiritual Competency

Abstract: Using narrative inquiry, the author explored the multicultural aspects of religious and spiritual experiences, assumptions, and patterns of 9 counselor educators to understand the impact that experiences and beliefs have when supervising and teaching counseling students. A gap exists between counselor standards, ethics, competencies, and practice, because counseling students receive mixed messages about addressing spiritual and religious concerns. Through hermeneutic analysis, 6 themes emerged: (a) religious a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Supervisors also develop competency through collaboration and consultation with appropriate religious leaders (McMinn, Snow, & Orton, ). It is interesting that the religious and spiritual competency of supervisors may be related to their own religious and spiritual development (Johns, ). Spiritually and religiously competent supervisors are better equipped to assist supervisees in addressing how their spiritual beliefs may be affecting the counseling relationship (Berkel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Supervisors also develop competency through collaboration and consultation with appropriate religious leaders (McMinn, Snow, & Orton, ). It is interesting that the religious and spiritual competency of supervisors may be related to their own religious and spiritual development (Johns, ). Spiritually and religiously competent supervisors are better equipped to assist supervisees in addressing how their spiritual beliefs may be affecting the counseling relationship (Berkel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…From a larger narrative research study on spirituality and counseling, (see Johns, 2014, 2017), six themes were identified, and the data poems were created through recursive and hermeneutic data analysis. Through the first research question, I sought to understand the personal religious and spiritual lived experiences of counselor educators.…”
Section: Methodological Notementioning
confidence: 99%
“…Although a handful of studies have examined the quantitative frequency of spiritual dialogue and how counselor educators’ experiences affect their discussions (Gilliam & Armstrong, 2012; Hull et al, 2013; Johns, 2017; Miller & Ivey, 2006; Miller et al, 2004), there are no known studies that explore what spiritual issues supervisees may have, including issues between supervisor and supervisee or between client and supervisee or internal spiritual issues the supervisee may be experiencing. Although we now know that spiritual issues exist and may be discussed, and that rapport is a factor (Weinstein, 2006), there remains a lack of understanding of what student supervisees experience regarding spiritual issues.…”
Section: Supervision In Counselor Training Programsmentioning
confidence: 99%